Exploring the Teachers’ Perspective on Morality in an English as a Foreign Language Pedagogy - Adriadi Novawan; Siti Aisyiyah; Alfi Hidayatu Miqawati; Fitri Wijayanti; Nodistya Septian Indrastana (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2020)
As a language of international communication, English is taught and learned in the contexts which are not neutral from morality or values both ESL and EFL. In the classroom contexts, there are interplays among diversity related to beliefs, religions, cultures, races, genders, ages, individual dispositions, and others. In Indonesia, values inculcation is nationally managed in the curriculum to accompany the offering subjects including English. However, to what extent it has been effectively incorporated in the EFL classroom has little been investigated. This research was aimed to reveal the reality of morality included in the EFL teaching in higher education based on the lecturers’ perspectives. Interviews were done to ten lecturers who were experienced in EFL teaching in a higher education institution. The findings revealed a solid consensus on the need of morality inclusion through the EFL pedagogy and its materials, nevertheless, its practices remained implicit. The study implied the need for specific studies on theoretical frameworks and instrumentation which guide teachers to incorporate values inculcation more sufficiently and sustainably into an EFL teaching.